Anna Arnold Hedgeman papers - Hedgeman, Anna Arnold, 1899-1990.
Correspondence, minutes of meetings, reports, speeches, organizational newsletters, and newspaper clippings documenting Hedgeman's activities on behalf of civil rights for African Americans and educational reform, and especially her efforts to continue the work of the U.S. Fair Employment Practices Committee following World War II.
African American civil rights leader and educator.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: United States. -- Fair Employment Practices Committee; African Americans -- Civil rights; African Americans -- Employment; Discrimination in employment -- United States; Educational change -- United States; Civil rights leaders; Educators